Challenges and Opportunities of Light-Emitting Diode (LED) as Key to Modulate Antioxidant Compounds in Plants. A Review - Martina Loi; Alessandra Villani; Francesco Paciolla; Giuseppina Mulè; Costantino Paciolla (Antioxidants, 2020)
Plant antioxidants are important compounds involved in plant defense, signaling, growth, and development. The quantity and quality of such compounds is genetically driven; nonetheless, light is one of the factors that strongly influence their synthesis and accumulation in plant tissues. Indeed, light quality affects the fitness of the plant, modulating its antioxidative profile, a key element to counteract the biotic and abiotic stresses. With this regard, light-emitting diodes (LEDs) are emerging as a powerful technology which allows the selection of specific wavelengths and intensities, and therefore the targeted accumulation of plant antioxidant compounds. Despite the unique advantages of such technology, LED application in the horticultural field is still at its early days and several aspects still need to be investigated. This review focused on the most recent outcomes of LED application to modulate the antioxidant compounds of plants, with particular regard to vitamin C, phenols, chlorophyll, carotenoids, and glucosinolates. Additionally, future challenges and opportunities in the use of LED technology in the growth and postharvest storage of fruits and vegetables were also addressed to give a comprehensive overview of the future applications and trends of research.